(untitled) (Eternitas: Jurnal Teknik Sipil, 2024)
Compaction is a crucial factor that affects the quality and performance of road pavements. This study evaluates the impact of varying compaction blows at the optimum asphalt content on Lataston (HRS-Base) mixtures using the Marshall Test method. The tested compaction variations are 2 x 40, 2 x 50, 2 x 60, and 2 x 70 blows. The results show that stability values increase from 841.19 kg at 2 x 40 blows to 1151.42 kg at 2 x 70 blows. Flow values decrease from 3.45 mm at 2 x 40 blows to 3.18 mm at 2 x 70 blows. The Marshall Quotient (MQ) increases from 243.85 kg/mm at 2 x 40 blows to 362.72 kg/mm at 2 x 70 blows. The Void in the Mineral Aggregate (VMA) decreases from 19.30% at 2 x 40 blows to 17.02% at 2 x 70 blows. The Void in Mix (VIM) also decreases from 5.22% at 2 x 40 blows to 2.54% at 2 x 70 blows. The Void Filled with Asphalt (VFA) increases from 72.94% at 2 x 40 blows to 85.10% at 2 x 70 blows. The density of the mixture increases from 2.271 gr/cm³ at 2 x 40 blows to 2.335 gr/cm³ at 2 x 70 blows. However, only the 2 x 50 blows variation meets all the parameters specified in Bina Marga 2018 Revision 2. The 2 x 40 blows compaction results in low MQ and high VIM, while the 2 x 60 and 2 x 70 blows compaction results in VIM below the minimum limit. These findings highlight the importance of balanced compaction to enhance road pavement quality.